Penataan Lahan Permukiman Dengan Metode Buffer Zone Untuk Kelestarian Lingkungan - Abdurrahman Abdurrahman (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
Previously known as Alalak’s hometown, it is now divided into two villages, namely South Alalak village and North Alalak village, located in North Banjarmasin District from 1970 to 2000. This area was famous as a center for the wood processing industry for building materials, but is now starting to be abandoned. dim because wood is also rare. Wooden materials were replaced with concrete beams, steel and metal rafters. Alalak Village looks very shabby, the houses are built mostly from irregular wood. However, there is something interesting in the Alalak River village which is visited by every local/regional, national and international holiday tourist. They wanted to witness the Floating Market activity as a rare custom in the form of buying and selling activities where sellers and buyers use boats or in the banjo term called catamarans. This empty village needs to be managed by building a riverside buffer area in the form of a long embankment with a width of 8.0 meters to 12.0 meters. The embankment material is planted with trees according to its purpose as protection from wind, waves and sunlight. The length of the embankment as a Buffer Zone for this building was built in stages in accordance with the budget set by the Banjarmasin City River and Drainage Department . Thinking about the need to organize dense residential and slum areas on the banks of this river from literature, videos about Buffer Zones in earthquake and tsunami prone areas in Japan which implement these zones as places of effort to withstand very large tsunami waves.